Аналіз економіко-математичних моделей монетарного стимулювання розвитку смарт-промисловості - Lohvinenko, Bohdan I. (Institute of Industrial Economics of NAS of Ukraine, 2024)
The article considers economic and mathematical models in the context of monetary stimulation of financial and economic development of the smart industry. The article analyses AD-AS, DSGE, VAR, CAPM, RBC, Phillips Curve and Cobb-Douglas models.The advantages and disadvantages of the models in the context of monetary stimulation of smart industry development are identified. The analysis has revealed that all the considered models have certain disadvantages, such as complexity of use and lack of clarity in interpreting the results, as well as limited consideration of factors that are important in monetary stimulation of the smart industry.The reviewed VAR model is limited in taking into account all factors affecting economic variables and is sensitive to specification, which leads to significant changes in the final results depending on the included variables and their specification. The CAPM model is based on assumptions about market efficiency that do not always correspond to reality, while the RBC model is characterised by the absence of instability and unrealistic assumptions about market behaviour. The Phillips Curve model shows instability when inflation and unemployment respond to economic shocks in different ways, which is unacceptable in the context of monetary stimulation for the development of the smart industry. The analysis identified the advantages and disadvantages of all models, which allowed us to objectively assess the actual conditions of the models.The analysis has shown that, given the above shortcomings and the specifics of the current economic environment, the Cobb-Douglas model is the most effective for analysing and forecasting the development of the smart industry in Ukraine.The other models considered may also be useful for stimulating the development of the smart industry, but they do not provide the same flexibility and ease of use as the Cobb-Douglas model. Thus, given the specifics of monetary policy, the Cobb-Douglas model seems to be the most appropriate tool for analysing and forecasting monetary stimulus for the development of the smart industry in Ukraine. It allows for a wide range of production factors and is simple to analyse and interpret the final results, making it the most suitable for addressing complex issues of monetary stimulation in the context of smart industry development.